Turbulence statistics above and within two Amazon rain forest canopies - Kruijt, Bart J.; Malhi, Yadvinder Singh; Lloyd, Jon; Nobre, Antônio Donato; Miranda, Antônio Carlos de Oliveira; Pereira, Maria G.P.; Culf, Alistair D.; Grace, John (Boundary-Layer Meteorology, 2000)
The turbulence structure in two Amazon rain forests was characterised for a range of above-canopy stability conditions, and the results compared with previous studies in other forest canopies and recent theory for the generation of turbulent eddies just above forest canopies. Three-dimensional wind speed and temperature fluctuation data were collected simultaneously at up to five levels inside and above two canopies of 30-40 m tall forests, during three separate periods. We analysed hourly statistics, joint probability distributions, length scales, spatial correlations and coherence, as well as power spectra of vertical and horizontal wind speed. The daytime results show a sharp attenuation of turbulence in the top third of the canopies, resulting in very little movement, and almost Gaussian probability distributions of wind speeds, in the lower canopy. This contrasts with strongly skewed and kurtotic distributions in the upper canopy. At night, attenuation was even stronger and skewness vanished even in the upper canopy. Power spectral peaks in the lower canopy are shifted to lower frequencies relative to the upper canopy, and spatial correlations and coherences were low throughout the canopy. Integral length scales of vertical wind speed at the top of the canopy were small, about 0.15 h compared to a value of 0.28 h expected from the shear length scale at the canopy top, based on the hypothesis that the upper canopy air behaves as a plane mixing layer. All this suggests that, although exchange is not totally inhibited, tropical rain forest canopies differ from other forests in that rapid, coherent downward sweeps do not penetrate into the lower canopy, and that length scales are suppressed. This is associated with a persistent inversion of stability in that region compared to above-canopy conditions. The inversion is likely to be maintained by strong heat absorption in the leaves concentrated near the canopy top, with the generally weak turbulence being unable to destroy the temperature gradients over the large canopy depth.
Keywords: Canopy; Skewness; Tropical Forest; Turbulence